Análisis de la razonabilidad del inventario y su incidencia en los estados financieros de la Empresa ASISCONSA S.A - Camacho Salazar, Katherine Yuridia (2024)
The presented Thesis Work deeply analyzes the exponential growth of inventories in the telecommunications company ASISCOMSA S.A., attributed to the increase in global demand in this sector. The reasonableness and optimal level that the inventory should have is studied in detail, as well as its impact on the main financial statements of the company, with the aim of optimizing inventory management. The great importance and relevance of this study in the current Ecuadorian business context is highlighted. Likewise, the need for greater and better training of personnel working in the warehouse area is suggested, in order to improve related processes and controls. The work carries out a deep analysis of the current situation of inventory management within the company, including findings related to the frequency and methods used for the physical counts of inventories. In this sense, problems and high variability in the form are evidenced. Additionally, results are presented........